Tratamento cirúrgico de ameloblastoma: relato de caso clínico - Araujo, Alexandre Carvalho de (Brasil, 2022)
Ameloblastoma is a benign odontogenic tumor, it has a slow but aggressive growth. It is one of the most commonly found tumors, being aggressive and with high rates of recurrence if not treated correctly. Treatment consists of being conservative or radical, where conservatives advocate curettage and marsupialization of the lesion, and the radical consists of partial or total resection of the mandible. The present study aimed to report a clinical case of surgical treatment of an ameloblastoma in the mandible through marginal resection surgery. 33 years old, female, patient, months later, and complaint of “feeling old, big patient”, with evolution in the region of approximately 6 months and complaint of “feeling of great age”, with evolution of approximately 6 months. Prior to seeking care at the Hospital Universitario Getúlio Vargas, she underwent an incisional biopsy and decompression procedure. Radiographic examination revealed extensive involvement of the body region and the left coronoid process, with a radiolucent image and impacted molar involvement. The proposed treatment consisted of marginal resection of the mandible on the left side, installation of a reconstruction plate under general anesthesia and application of charcoal solution. The same patient was discharged one day after surgery and seven days later, she returned to the oral and maxfacial surgery outpatient clinic, due to a receipt of a case, requiring a new admission to intravenous antibiotic therapy. After the resolution of the condition, a patient continued in postoperative follow-up and currently five years after the surgery, the same is without clinical signs and the same recurrence of the radiographic lesion. Effectiveness of the above, it was concluded that the treatment of ameloblastoma can be done with the treatment of resection with a safety margin, installation of reconstruction plate and application of Carnoy's solution.